Bovine Respiratory Syncytial Virus Enhances the Adherence of Pasteurella multocida to Bovine Lower Respiratory Tract Epithelial Cells by Upregulating the Platelet-Activating Factor Receptor - Sudaryatma, Putu Eka; Saito, Akatsuki; Mekata, Hirohisa; Kubo, Meiko; Fahkrajang, Watcharapong; Mazimpaka, Eugene; Okabayashi, Tamaki (Frontiers in Microbiology, 2020)
Coinfection by bovine respiratory syncytial virus (BRSV) and Pasteurella multocida (PM) frequently has been observed in cattle that develop severe pneumonia. We recently reported that BRSV infection significantly increased PM adherence to bovine lower respiratory tract epithelial cells. However, the molecular mechanisms of enhanced PM adherence are not completely understood. To investigate whether BRSV infection regulates any cellular adherence receptors on bovine bronchus- and lung-epithelial cells, we performed proteomic and functional analyses. The proteomic analysis showed that BRSV infection increased the accumulation of platelet-activating factor receptor (PAFR) in both cell types. Molecular experiments, including specific blockade, knockdown, and overexpression of PAFR, indicated that PM adherence to these cell types depended on PAFR expression. These findings highlight the role, in cattle with severe pneumonia, of the synergistic effect of coinfection by BRSV and PM in the lower respiratory tract.